2015
DOI: 10.4236/jssm.2015.82019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transport Time of up to 12 Hours on Welfare of Cows and Bulls

Abstract: The aim of the study was to investigate the effects of transport time up to 12 h on welfare of bulls and cows. Cattle transport vehicle was used for the experiment. Sensors to measure temperature, relative humidity and video camera to monitor behaviour were mounted in observation pen. Eighteen measurements were performed during summer and winter for 4, 8, and 12 h transport time with three replications. To determine cortisol, glucose, lactate, and creatine kinase concentrations, blood samples were collected be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 31 publications
1
12
0
11
Order By: Relevance
“…Effects revealed after longer transport distances can potentially cause a decrease in the cortisol response that may be due to the extensive fasting or exhaustion associated with the journey (Van Engen et al ., 2014). Supporting results indicated that increased transport time correlated with a decrease in the level of plasma cortisol concentration (Gebresenbet et al ., 2012; Bulitta et al ., 2015). This change could be caused by the animal's acclimation to transport.…”
Section: Biomarkers Of Stressmentioning
confidence: 99%
“…Effects revealed after longer transport distances can potentially cause a decrease in the cortisol response that may be due to the extensive fasting or exhaustion associated with the journey (Van Engen et al ., 2014). Supporting results indicated that increased transport time correlated with a decrease in the level of plasma cortisol concentration (Gebresenbet et al ., 2012; Bulitta et al ., 2015). This change could be caused by the animal's acclimation to transport.…”
Section: Biomarkers Of Stressmentioning
confidence: 99%
“…Berdasarkan hasil penelitian, diketahui bahwa rataan nilai THI di KPT Maju Sejahtera adalah 83,58, dengan rataan nilai THI terendah dan tertinggi berturut-turut pada pukul 06.00 dan 12.00 WIB yaitu sebesar 77,55 dan 86, 65. Menurut Bulitta et al (2015), representatif kondisi ternyaman ternak apabila nilai THI suatu lingkungan kandang ≤74. Sementara ternak yang dianggap mengalami stress ringan--sedang apabila nilai THI berkisar antara 75--83 dan ternak mengalami stress berat apabila nilai THI≥84.…”
Section: Hasil Dan Pembahasan Kondisi Suhu Udara Dan Kelembaban Lingk...unclassified
“…Beberapa peneliti melaporkan bahwa kegiatan transportasi seperti persiapan pengangkutan, pemuatan, transportasi dan pembongkaran ternak yang dilakukan oleh para pengusaha ternak menggunakan kapal laut, truk atau transportasi lainnya umumnya dapat mengakibatkan stres (Genswein et al, 2012;Aradom, 2013;Bulitta et al, 2015). Selanjutnya dijelaskan bahwa beberapa faktor utama penyebab stres pada ternak selama transportasi adalah karakteristik mikroklimat atau faktor meteorologis (temperatur, kelembaban, kecepatan angin dan radiasi matahari) dan faktor non meterorologis (penanganan ternak pada saat loading/unloding, lama pelayaran/perjalanan, getaran, desain alat transportasi, kepadatan ternak, kuantitas dan kualitas pakan yang diberikan serta ketersediaan air minum).…”
Section: Pendahuluanunclassified